EFFECT OF IT GOVERNANCE, CONTINUOUS AUDITING AND IT GOALS ALIGNMENT TO COMPANY’S PERFORMANCE (Study on Plantation Companies in the Group of PT. Astra Agro Lestari Tbk in Riau) - Nafisah Syafei (JURNAL AL-IQTISHAD, 2015)
The purpose of this study is to examine the effect of IT governance, continuous auditing, and the IT goals alignment to company’s performance. This study also examined the effect of IT governance to IT goals alignment, the effect of IT governance to continuous auditing, and the effect of IT goals alignment to continuous auditing. Research conducted on the plantation companies in the group of PT. Astra Agro Lestari, Tbk in Riau that have used the information system ERP (Enterprise Resource Planning) to integrate and automate business processes. Population of this study included all managers in these plantation companies.  Sampling was  conducted  by purposive  sampling that  take samples  from thecertain  level  managers who  are in the  top level of  main  structure of the  six companies  in these companies plantation group.  Data processing  is done  to  40  questionnaires returned  byrespondents using  PLS  analysis  (Partial Least  Square). Results of hypothesis testing at the 0.05 significance level indicates that the IT governance, continuous auditing, and the IT goals’s alignment affect the company's performance. IT governance affects on the IT goals’s alignment and IT governance also affect on the continuous auditing, while the alignment of IT goals has no effect on continuous auditing.